Effects of biochar application on soil nitrogen transformation, microbial functional genes, enzyme activity, and plant nitrogen uptake: A meta‐analysis of field studies - Zhang, Leiyi; Jing, Yiming; Chen, Chengrong; Xiang, Yangzhou; Rezaei Rashti, Mehran; Li, Yantao; Deng, Qi; Zhang, Renduo (Global change biology. Bioenergy, 2021)
Biochar application can influence soil nitrogen (N) cycle through biological and abiotic processes. However, studies on comprehensive examination of the effects of biochar application on microbially mediated N‐cycling processes (N mineralization, nitrification, denitrification, and fixation) and soil N fate (i.e., plant N uptake, soil N2O emission, and N leaching) are warranted. Therefore, the aim of this study was to examine the effects of biochar application on soil N transformation, microbial functional gene abundance, enzyme activity, and plant N uptake. To achieve the objective of this study, a meta‐analysis involving 131 peer‐reviewed field experiments was conducted. Results showed that field application of biochar significantly enhanced soil NH4+ and NO3‐ content, N mineralization, nitrification, N2 fixation, and plant N uptake by 5.3%, 3.7%, 15.3%, 48.5%, 14.7%, and 18.3%, respectively, but reduced N2O emissions and N leaching by 14.9% and 10.9%, respectively. Biochar application also increased the abundance of soil denitrifying/nitrifying genes (amoA, narG, nirS/nirK+S, and nosZ), proportion of N2 fixation bacteria, and N‐acetyl‐glucosaminidase activity by 18.6%–87.6%. Soil NO3‐ content was positively correlated with AOA‐amoA abundance, and soil N2O emission was positively correlated with the relative abundance of genes (e.g., amoA, narG, and nirS/nirK) involved in N2O production. Furthermore, long‐term biochar application tended to increase AOB‐amoA and nirK+S abundance, especially soil N2O emission and N leaching. Overall, the findings of this study indicated that biochar application accelerated microbially mediated N‐cycling processes under field conditions, thereby enhancing soil N availability and plant productivity. However, long‐term biochar application may increase N losses. Therefore, future studies should be conducted to examine the effect of long‐term biochar application on the soil N cycle and the underlying microbial mechanisms. Based on a meta‐analysis, this study showed that biochar application accelerated microbially mediated N‐cycling processes (i.e., mineralization, nitrification, denitrification, and fixation), which improved soil N availability and plant N uptake. Especially, biochar application (load of 21–40 t ha−1) to soil was more favorable for enhancing N‐relevant microbial gene abundance and enzyme activity. However, long‐term biochar application may increase N losses. A decrease in biochar N adsorption with increase in treatment duration could pose potential ecological risk in the long run.